Leaders, leadership and future primary care clinical research - Furler, J; Cleland, J; Del Mar, C; Hanratty, B; Kadam, U; Lasserson, D; McCowan, C; Magin, P; Mitchell, C; Qureshi, N; Rait, G; Steel, N; et al. (BioMed Central, 2008)
Background: A strong and self confident primary care workforce can deliver the highest quality care and outcomes equitably and cost effectively. To meet the increasing demands being made of it, primary care needs its own thriving research culture and knowledge base. Methods: Review of recent developments supporting primary care clinical research. Results: Primary care research has benefited from a small group of passionate leaders and significant investment in recent decades in some countries. Emerging from this has been innovation in research design and focus, although less is known of the effect on research output. Conclusion: Primary care research is now well placed to lead a broad re-vitalisation of academic medicine, answering questions of relevance to practitioners, patients, communities and Government. Key areas for future primary care research leaders to focus on include exposing undergraduates early to primary care research, integrating this early exposure with doctoral and postdoctoral research career support, further expanding cross disciplinary approaches, and developing useful measures of output for future primary care research investment.